Discontinuous strain-induced martensite transformation related to the Portevin-Le Chatelier effect in a medium manganese steel. (May 2017) - Sun, Binhan; Vanderesse, Nicolas; Fazeli, Fateh; Scott, Colin; Chen, Jianqiang; Bocher, Philippe; Jahazi, Mohammad; Yue, Stephen
Abstract: The correlation between the strain-induced martensite transformation (SIMT) and the Portevin-Le Chatelier (PLC) effect during tensile testing of a ferrite-austenite duplex medium manganese (Mn) steel was investigated in this study. A discontinuous SIMT phenomenon (D-SIMT) was observed in the steel by in situ magnetic induction measurements complemented with ex situ X-ray diffraction analysis. This unique behavior was due to the localized martensite formation in the PLC bands forming and propagating continuously during tensile straining. The PLC bands were characterized by the digital image correlation technique and their origin is further discussed. Graphical abstract: